Ibrutinib - Charalambous, Andriani; Schwarzbich, Mark-Alexander; Witzens-Harig, Mathias (Small molecules in hematology, 2018)
Abnormal B-cell receptor (BCR) signalling is a key mechanism of disease progression in B-cell malignancy. Bruton’s tyrosine kinase (BTK) has a pivotal role in BCR signalling. Ibrutinib (PCI-32765) is a small molecule which serves as a covalent irreversible inhibitor of BTK. It is characterized by high selectivity for BTK and high potency. Ibrutinib is currently approved by the FDA and EMA for use in chronic lymphocytic leukaemia in any line of treatment, for treatment of Waldenstrom macroglobulinemia in patients who have received previous treatments or are not suitable to receive immunochemotherapy as well as for second line treatment of mantle cell lymphoma and for patients with marginal zone lymphoma who have received at least one prior anti-CD20-based therapy. In addition, there is emerging clinical data on its efficacy in ABC subtype diffuse large B-cell lymphoma, multiple myeloma and primary central nervous system lymphoma. Ibrutinib has opened new options for treatment of those patients that have relapsed or have been refractory to more classical modes of treatment. Moreover, Ibrutinib has been shown to be effective in patients that have been known to have little sensitivity to classical immunochemotherapy. Having a favourable risk profile, the substance is, unlike conventional immunochemotherapy, also suitable for the less physical fit patients. Cases of primary and secondary resistance to Ibrutinib have emerged and there is an ongoing effort to identify their mechanism and develop strategies to overcome them. Beyond its direct effects on survival and apoptosis of malignant B-cells, there is increasing evidence that Ibrutinib is able to modulate the tumour microenvironment to overcome mechanisms of immune evasion. This has sparked interest in use of the substance beyond lymphoid malignancy. This chapter discusses structure, mechanism of action and toxicities of Ibrutinib and also presents important preclinical and clinical data as well as mechanisms of Ibrutinib resistance. Combination strategies with immunotherapeutic strategies such as immune checkpoint blockade and CAR T-cell therapy may be synergistic and are currently under investigation.